URGENSI SEKOLAH PAUD UNTUK TUMBUH KEMBANG ANAK USIA DINI - Raihana Raihana (UIR PRESS, 2018)
Early childhood education institutions are one form of early childhood education in formal education pathways for zero to six years. Early childhood education, in essence is education that is organized with the aim to facilitate the growth and development of children as a whole or emphasize the development of all aspects of the child's personality. Therefore, education for early childhood especially kindergarten needs to provide various activities that can develop various aspects of development which include cognitive, language, social, emotional and physical. Growth and development are a process that occurs in every living creature naturally. Growth will undergo physical changes while the development of changes in the structure and function of the body more complex. Children are individuals who are in a range of developmental changes ranging from infancy to adolescence.